Knowledge and perception regarding prenatal genetic screening of thalassemia, down syndrome and neural tube defects: a study among IIUM Kuantan undergraduates - Sulaiman, Nur Sajidah; Zainuddin, Norafiza (Malaysian Public Health Physicians’ Association, 2018)
Prenatal genetic screening is offered during pregnancy to detect foetuses that have certain diseases. It is widely used in the detection of congenital malformation which results in foetal birth defects. Unawareness of the society on the importance of prenatal genetic testing contributes to the increase in the birth defect rate.Future parents should be exposed with the importance in performing prenatal genetic screening.The purpose of this study was to examine the knowledge and perception level of International Islamic University Malaysia (IIUM) Kuantan students regarding prenatal genetic screening thalassemia, Down syndrome and neural tube defects.This is a cross-sectional study whereby192 respondents were selected using convenience sampling method. A set of close-ended questionnaire was distributed among students in IIUM Kuantan. Independent t-test, parametric test (One- Way ANOVA test), non-parametric test (Mann-Whitney test) and correlation coefficient (Pearson) were used to find all related factors influencing knowledge and perception and to find association between knowledge and perception of IIUM Kuantan students.From this study, it was found that the level of knowledge and perception of IIUM Kuantan students regarding prenatal genetic screening of thalassemia, Down syndrome and neural tube defects was relatively high. Married students hada betterknowledge compared to unmarriedstudents (p=0.008). Moreover, students from Kulliyyah (Faculty) of Medicine had adequate level of knowledge (p<0.001) and good perception (p=0.003) compared to students from other kulliyyahs. Age and year of study weresignificantly associated with students’ knowledge (p<0.001). In addition, ageand year of study were significantly associated with students’ perception(p=0.03 and p=0.007, respectively). The findings of this study depicted that adequate level of knowledge has ledto a good perception towards prenatal genetic screening among IIUM undergraduate students (p<0.001). Keywords: Prenatal genetic screening, undergraduate students, knowledge, perception, Malaysia.